Solvent-controlled regioselective protection of allyl-4,6-benzylidene glucopyranosides - Ness, Kerry Ann; Migaud, Marie E. (Beilstein Journal of Organic Chemistry, 2007)
We wish to report a simple synthetic procedure, which permits the regiospecific mono-acylation, alkylation and silylation at the 2-position of allyl 4,6-O-benzylidene α-D-glucopyranoside in high yields and which does not require the use of catalysts.